Hubungan Antara Paritas Dan Pantang Makan Terhadap Kejadian Kekurangan Energi Kronik (KEK) Pada Ibu Hamil Di Puskesmas Kota Bandar Lampung - Rachmi L.P. Rukmono; Dian Isti Angraini; Tri Umiana Soleha (Medula, 2020)
Chronic energy deficiency (CED) is defined as the condition of the occurrence of health problems, due to suffering from chronic food shortages. CED prevalence in Indonesia for pregnant women aged 15-49 years is 24.5%. The prevalence of CED in Bandar Lampung was the second highest after East Lampung which is 24.5%. The incidence of CED in pregnant women is influenced by direct factors and indirect factors. This research aimed to indentify the relationship of parity and food taboo to CED in pregnant women in Primary Health Center of Bandar Lampung. This research method used a cross-sectional method. The sampling technique is random sampling. The study was conducted in August-November 2018, at six health primary centers in Bandar Lampung. The sample obtained 88 pregnant womens. The diagnosis of CED is based on LILA <23.5 cm, whereas for food taboo and parity according to the questionnaire that has been made. The results showed that mothers had CED of 40.9% and not CED of 59.1%. The results of bivariate analysis on the food taboo variable obtained p value of 0.001 (p <0.05), which means that there was a relationship between food taboo and incidence of CED in pregnant women. While the parity variable was p value of 0.5179 (p> 0.05) no significant relationship between significant parity in the incidence of CED in pregnant women.